A Perylene diimide based fluorescent probe for caffeine in aqueous medium. Issue 1 (2nd January 2019) - Karmakar, Parthasarathi; Manna, Srimanta; Maiti, Kalipada; Ali, Syed Samim; Guria, Uday Narayan; Sarkar, Ripon; Datta, Pallab; Mandal, Debasish; Mahapatra, Ajit Kumar
ABSTRACT: Caffeine is a legal stimulant drug which has received considerable attention due to its widespread use as a beverage and in pharmaceutical formulations. However, reported chemosensors for caffeine are limited. In the present study use of a perylene diimide (PDI) derivative has been explored for the first time for detection and quantification of caffeine in an aqueous medium. Spectroscopic studies (UV-Vis, Fluorescence, FTIR and 1H-NMR) suggest that aspartic acid modified perylene diimide (PASP ) may bind to caffeine through π-π interaction. This interaction results in immediate quenching of fluorescence and optical color change which can be perceived through naked eyes. This probe has been successfully used for bio-imaging of caffeine in living cells. Graphical Abstract: